2018
DOI: 10.1021/acs.biomac.8b00829
|View full text |Cite
|
Sign up to set email alerts
|

Fucose-Functionalized Precision Glycomacromolecules Targeting Human Norovirus Capsid Protein

Abstract: Norovirus infection is the major cause of nonbacterial gastroenteritis in humans and has been the subject of numerous studies investigating the virus's biophysical properties and biochemical function with the aim of deriving novel and highly potent entry inhibitors to prevent infection. Recently, it has been shown that the protruding P domain dimer (P-dimer) of a GII.10 Norovirus strain exhibits two new binding sites for l-fucose in addition to the canonical binding sites. Thus, these sites provide a novel tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Additionally, three trivalent structures ( 3 , 6 , and 7 ) were synthesized containing one, two, or three EDS spacer building blocks between the fucose units, respectively. It should be noted that the fucosylated glycooligomers in solution most likely adapt a coiled conformation as was previously shown, for example, by dynamic light scattering experiments . The hydrodynamic volume of such coiled structures would be expected to also depend on the overall length of the scaffold.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Additionally, three trivalent structures ( 3 , 6 , and 7 ) were synthesized containing one, two, or three EDS spacer building blocks between the fucose units, respectively. It should be noted that the fucosylated glycooligomers in solution most likely adapt a coiled conformation as was previously shown, for example, by dynamic light scattering experiments . The hydrodynamic volume of such coiled structures would be expected to also depend on the overall length of the scaffold.…”
Section: Resultsmentioning
confidence: 69%
“…Building blocks TDS and EDS were synthesized following known procedures . Fucosylated oligoamides were synthesized according to the previously established protocols via solid phase polymer synthesis (SPPoS) on a Tentagel S‐RAM resin with a loading of 0.22–0.25 mmol g −1 (for detailed information, see Supporting Information) . In short, via alternating coupling and deprotection steps with EDS as spacer and TDS as functional building block, the targeted scaffold structures were build‐up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other direct binding assays using various scaffolds such as dendrimers or nanoparticles as scaffolds also mainly showed additive effects due to the multivalent presentation of carbohydrates, but not positively cooperative interactions due to chelate‐like binding or subsite binding to the receptor. To shed more light on the molecular mechanisms of carbohydrate binding X‐ray crystallography, or single molecule techniques based on labeled carbohydrates for NMR spectroscopy and single molecule AFM were used. For example, Drescher and coworkers showed that flexible PEG‐based ligand scaffolds can stretch to accommodate an additional binding site after binding to a first site at a carbohydrate binding protein .…”
Section: Effect Of Ligand Presentation On the Affinity Of Carbohydratmentioning
confidence: 99%
“…This is due to the interplay of various molecular parameters, for example, non‐specific interactions of the ligand backbone, conformation and flexibility of the scaffold, receptor subsite binding, as well as receptor clustering and formation of multireceptor complexes . There are, however, a few examples were simultaneous chelate‐like binding to lectins and pathogenic receptors was observed, which allowed for direct correlation between affinity and structure of the ligands. These studies used advanced structural analysis of the carbohydrate–protein complexes by X‐ray crystallography or nuclear magnetic resonance (NMR) spectroscopy to show simultaneous binding of carbohydrate subunits.…”
Section: Introductionmentioning
confidence: 99%